2019
DOI: 10.1186/s42483-019-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals pathways facilitating the growth of tobacco powdery mildew in Arabidopsis

Abstract: Powdery mildew (PM) fungi are biotrophic pathogens that rely on living hosts to survive and thrive. However, their colonization is restricted by host defenses at both the penetration and post-penetration stages. The tobacco PM strain Golovinomyces cichoracearum (Gc) SICAU1 has overcome penetration resistance of Arabidopsis but its growth is arrested by post-penetration resistance. While Gc SICAU1 only poorly grows in Arabidopsis Col-0 wild-type plants, it can sustainably grow for more than 20 days on the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
5
1
Order By: Relevance
“…In our experiment, this is also an intriguing biological phenomenon that highlights the complexity of obligate biotrophic plant-pathogen interactions who are direct target of the CmbHLH87 protein and how to interact in response to pathogen resistance need to be further research. PM symptoms herein were observed in WT tobacco seedlings at 7 dpi of G. cichoracearum, and the phenotypes were not more robust than those of previous reports: PM disease occurs abundantly in tobacco plants at 12 dpi of the PM strain G. cichoracearum SICAU1 (Li et al, 2019). Different tobacco accessions may show various susceptible PM disease phenotypes to different PM isolates.…”
Section: Discussioncontrasting
confidence: 75%
“…In our experiment, this is also an intriguing biological phenomenon that highlights the complexity of obligate biotrophic plant-pathogen interactions who are direct target of the CmbHLH87 protein and how to interact in response to pathogen resistance need to be further research. PM symptoms herein were observed in WT tobacco seedlings at 7 dpi of G. cichoracearum, and the phenotypes were not more robust than those of previous reports: PM disease occurs abundantly in tobacco plants at 12 dpi of the PM strain G. cichoracearum SICAU1 (Li et al, 2019). Different tobacco accessions may show various susceptible PM disease phenotypes to different PM isolates.…”
Section: Discussioncontrasting
confidence: 75%
“…Two lines (TaSTP6-OE1 and TaSTP6-OE2) showing distinct TaSTP6 mRNA accumulation in leaves (Supplemental Fig. S10) were inoculated with powdery mildew (Li et al, 2019), which resulted in an enhanced susceptibility phenotype (Fig. 4A).…”
Section: Overexpression Of Tastp6 Promotes Arabidopsis Susceptibilitymentioning
confidence: 99%
“…A previous study on Arabidopsis has shown the involvement of MAPK signaling pathway against PM infection [25]. The KEGG pathway enrichment analysis also indicated that 101 DEGs were enriched in this pathway.…”
Section: B Mapk Signaling Pathway and Toll-like Receptor Signaling Pa...mentioning
confidence: 64%